THE IMPLEMENTATION OF MAKE A MATCH METHOD TO INCREASE STUDENTSâ€™ ABILITY IN WRITING PROCEDURE TEXT - Nasyiatul Aisyah (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
The mastery of English in senior high school including four skills i.e:listening, speaking, reading and writing. They are supported by vocabulary,structure and pronounciation. From four skills above, writing is one of the skillsâ€™problem for the students in learning process.It can be seen from the studentsâ€™mark to express their ideas in making the procedure text. It is about 60% under grade (KKM). This problem makes the writer interested to solve. The writer wants to analize the studentsâ€™ability in writing the procedure text by using make a match methode. The research was purposed to increase the studentsâ€™ ability to write the procedure text, to develop learningâ€™s strategy, and learning methode which is effective, effisien and fun. The students can participate actively in learning process.The students can express their ideas and feelings orally and writing. Technique used in this research is observation, monitoring, and performance test in writing test. The result showed that 72% active in learning process. There was only a student who was still under grade. The result of post test there were 2 students ( 0,07%) who got C â€œgoodâ€ 15 students (0,41%) got D â€˜fairâ€™, 18 siswa (0,49%) got E â€˜poorâ€™Keyword: makea match methode,writing ability,procedure text